Imaging features for diffuse-type tenosynovial giant cell tumor of the temporomandibular joint: A case report. Issue 26 (June 2017) - Hu, Yan; Kuang, Bin; Chen, Yue; Shu, Jian
Abstract: Rationale: The tenosynovial giant cell tumor (TGCT) is a benign but locally aggressive tumor that arises from the synovial membrane of joints, tendon sheaths, and bursae. Although any joint can be affected, involvement of the temporomandibular joint (TMJ) was reported very rarely, and there is no relevant report on 18 F-FDG PET/computerized tomography (CT). Patient concerns and diagnoses: We present here a rare case of diffuse-type of TGCT (D-TGCT) arising from the right TMJ in a 74-year-old woman. The patient was discovered a mass of the right temporal fossa during a head CT scan. However, she did not receive any treatment and was discharged from the hospital. She visited our institution again after 4 years with worsening headache and swelling of the right preauricular area. An enhanced CT demonstrated a 6.0 × 3.4 × 5.0 cm mass of mixed density involving the right TMJ, with evident enhancement and extensive erosion of adjacent bones. Magnetic resonance imaging (MRI) showed hypointensity in the solid part of the mass but high signal intensity in the cystic part or necrosis on T2-weighted images (T2WI). In 18 F-FDG PET/CT images, the solid portion of the mass had increased FDG uptake with a SUVmax of 19.8. It was then diagnosed as D-TGCT by postoperative pathology. Lessons: The case report shows the imaging features of the TGCT, including CT, MRI, and 18 F-FDG PET/CT, especially the typical hypointensity on T2WI. Careful preoperative examination and complete resection are the factors that lead to the optimal treatment of the TGCT.